Building Cooperation in Post-Conflict Areas : Rwanda Community Reintegration and Development Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
In Rwanda, postwar poverty is widespread, especially in the rural regions. The World Bank-supported Rwanda Community and Reintegration and Development Project is a best practice example of promoting the social and economic integration of the poor amid ethnic tensions in a post-conflict situation. This project embodies Social Development best practice elements, identified as Multi-dimensional approach to poverty reduction aimed at enhancing opportunities, capabilities, empowerment, and security of the poor; institutionalized mechanisms for participation and decentralized implementation; and ongoing monitoring and evaluation of social development outcomes by the government and community.